Alternative economic survey 2001-2002 economic "reforms" : development denied (Noida, U.P. Rainbow Publishers, 2002)
Contributed articles on Indian economy post 1991 liberalization and structural adjustment process.
From gradual to galloping liberalization: a journey to nowhere to withering - Kamal Nayan Kabra The economic slowdown: Growing disparities, Globalization, and the black economy - Arun Kumar Regional growth and disparities - Ravi S. Srivastava Agriculture: Pramod K. Chaubey Agricultural Labourers - S. P. Singh Industry - T. Ravi Kumar Sickness in Indian industry - Pushpa Kumari Public enterprises - R.K.Mishra, B. Navin and P. Geeta Privatization - Ashok Rao Financial sector - Hari Om Verma 2003 - 03 Budget - Atul Sood Stock market - K.S. Chalapati Rao Balance of payments - Sunanda Sen External sector - Manmohan Krishna Intellectual property Regime - Biswajit Dhar Telecom - Arun Mehta Prices and the PDS - V. Upadhyay Hunger and starvation - Shalini Kala and Aasha Kapur Mehta The urban sector - T.M. Thomas Unemployment P.K. Chaubey Employment and casualisation - Bansari Choudhury Gender issues - Navsharan Singh Higher education - Jandhyala B. G. Tilak Elementary education - Sadhna Saxena Health - Alpana Sagar and Imrana Quadeer Media - Sanjay Kapoor Labour's resistance to reforms - Souparna Lahiri Governance - Kamala Prasad Reforms, Governance and the state of the people - Dolly Arora
Keywords: STRUCTURAL ADJUSTMENT (ECONOMIC POLICY); ECONOMICS